Spring phenological models combining the effects of temperature and photoperiod are successfully transferred to various spatial and temporal scales: a case study of Aesculus hippocastanum L. - Korsakova Svetlana; Korsakov Pavel; Evstigneev Vladislav (Folia Oecologica)
On the basis of long-term, high-quality in situ observations on phenological and meteorological data, we parameterised and examined the performances of four single-phase and two two-phase models for the prediction of the leaf unfolding and flowering dates of horse chestnut (Aesculus hippocastanum L.). Amongst models, those combining the effects of temperature and photoperiod showed the best phenophase prediction, suggesting the influence of photoperiod on the leaf unfolding and flowering of A. hippocastanum. The obtained coefficients showed that the effect of photoperiod was greater on leaf unfolding than on flowering. Comprehensive assessment revealed that the single-phase BCdoy model demonstrated the best fitting for both phenophases. This model also showed sufficiently high accuracy and the transferability of results in time and space. The proposed models can be used to predict the spring phenophases of A. hippocastanum in European and Asian countries, where this ornamental tree species is widely used in urban landscaping, and to optimise control methods against Cameraria ohridella Deschka & Dimić (Lepidoptera, Gracillariidae). For C. ohridella, the first flying out of adults after overwintering begins at the onset of horse chestnut leaf unfolding and mass flight occurs during the full flowering period.